Prevalence and Predictors of Self-Medication Practice Among Teachers’ Education Training College Students in Amhara Region, Ethiopia: A Cross-Sectional Study - Mekuria, Abebe Basazn; Birru, Eshetie Melese; Tesfa, Melkamu Teshome; Geta, Mestayet; Kifle, Zemene Demelesh; Amare, Tsegaw (Frontiers in Pharmacology, 2021)
Background: Self-medication practice is the use of medications without health care professional requests. It can lead to inappropriate medication usage, wastage of resources, increased chance of microbial resistance, and adverse drug reactions. Therefore, this study aimed at assessing the prevalence and associated factors of self-medication practice among teacher’s education training college students in the Amhara region, Ethiopia. Methods: A multicentre cross-sectional study was conducted on 344 teacher's education training college students in the Amhara region, Ethiopia, from January 1 to February 28, 2020. Data on socio-demography, the practice of self-medication as well as a factor associated with self-medication practise was collected through a self-administered structured questionnaire. Systematic random sampling was used to select participants. Descriptive statistics, univariate, and multivariate logistic regression analyses were done to determine various variables and factors associated with self-medication practice. Results: Out of 344 respondents, 234 (68.0%) were practiced self-medication. The most commonly cited indication for self-medication practice was headache 75 (32.05%) followed by abdominal discomfort 53 (22.6%). The respondents with the age of greater than 26 years (AOR: 2.47, 95% CI: 1.18-3.94), third years of study (AOR: 3.14, 95% CI: 1.94–5.79), urban residence (AOR: 2.97, 95% CI: 1.06-3.64), near accessibility of pharmacy (AOR: 2.12, 95% CI: 1.43-4.46) and who had peer/family pressure (AOR: 2.34, 95% Cl: 1.53-3.56) were significantly associated with self-medication practice. Conclusion: More than two-thirds of the study participants practiced self-medication. Being from an urban area, having access to a private pharmacy, and increase year of study positively affects self-medication practice.